Dependence of the clinical course of generalized periodontitis on the quality of occlusal balance after complex treatment. - V. G. Malynovskyi (Medičnì Perspektivi)
The purpose of this research was to study the features of the clinical course of generalized periodontitis, depending on the quality of occlusal balance after complex treatment. 128 patients with generalized periodontitis of the I-II degree, chronic course, aged 35-55 years, were examined. All of them underwent a clinical examination, computed tomography of the jaw bones, and occlusive diagnostics by means of the “T-scan III” device. As a result of the conducted studies, it was found that only in 34,4±4,2% of patients occlusal relationships were restored, whereas in the remaining 65,6±4,2% occlusion balance disorders were registered. The presence of occlusal imbalance was accompanied by a worsening of the clinical condition of periodontal tissues. It was shown that the greatest correlation is observed for the degree of occlusive imbalance with the index of osteoporosis activity (r=0.42, p<0.05), less significant – with Ramfjord indices (r=0.40, p<0.05), PI (r=0.38, p<0.05) and CPITN (r=0.35, p<0.05). Also, with disorders of occlusal balance, there was a decrease in bone mineral density, most pronounced in areas of hyperocclusion. At the same time, the revealed changes were not reliable (р˃0.05), which was explained by the focal nature of the appearance of resorptive phenomena in areas of increased occlusal load. According to obtained results, the qualitative restoration of occlusal ratios, in particular with the help of modern computer equipment, in the complex treatment of generalized periodontitis is the key to long-term clinical and X-ray stabilization of the disease.